Cutaneous amyloidosis in the orbital region (case report) - A.N. Bochkareva; V.V. Egorov; O.V. Kolenko; G.P. Smolyakova; P.A. Banshchikov (РМЖ "Клиническая офтальмология")
A.N. Bochkareva1, V.V. Egorov1,2, O.V. Kolenko1,2, G.P. Smolyakova1,2, P.A. Banshchikov1 1Khabarovsk Branch of the S.N. Fyodorov Eye Microsurgery Federal State Institution, Khabarovsk, Russian Federation 2Institute of Advanced Training of Healthcare Specialists, Khabarovsk, Russian Federation Amyloidosis is an extracellular mesenchymal dysproteinosis characterized by deposition of amyloid in tissues, parenchymal atrophy and functional organ failure leading to fatal outcomes. A significant problem of this disease for a doctor of any specialty remains a long period of establishing a clinical diagnosis. Insufficient awareness of the disease, due, among other things, to the extremely low incidence of patients with amyloidosis — today about 50 thousand people suffer from amyloidosis in the world. The article presents a clinical case of the early stage of primary systemic AL-amyloidosis affecting the eyelid skin bilaterally with further disease progression involving the skin of palms, soles and the oral mucosa. Among the types of amyloidosis described so far, the ocular adnexal involvement is an extremely rare finding which has such manifestations as periorbital cutaneous purpura and ecchymoses — “racoon eyes.” Timely diagnosis, the selection of individualized treatment strategies and the administration of chemotherapy would ensure clinical and hematological remission of amyloidosis, halt the disease progression, and thus reduce the probability of adverse outcome. The described clinical case has demonstrated that diagnosis of amyloidosis can be challenging, and that the disease has diverse and non-specific clinical manifestations. Keywords: amyloidosis, periorbital purpura, cutaneous ecchymoses, racoon, eyes, orbital amyloidosis, ocular adnexal amyloidosis, chemotherapy. For citation: Bochkareva A.N., Egorov V.V., Kolenko O.V. et al. Cutaneous amyloidosis in the orbital region (case report). Russian Journal of Clinical Ophthalmology. 2023;23(2):94–98 (in Russ.). DOI: 10.32364/2311-7729-2023-23-2-94-98.